ARTIFICIAL INTELLIGENCE IN EDUCATION: OPPORTUNITIES AND CHALLENGES - RYMAR, BOHDAN; HOBYR, LIDIIA; VAVRYK, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article highlights the significant impact of artificial intelligence (AI) on the transformation of the educational process in the modern world. The author conducts an in-depth analysis of the main areas of use of AI technologies in the field of education, including adaptive educational platforms, automated assessment of student knowledge, and promoting inclusion for participants in the educational process with various physical, cognitive, or social needs. The study examines examples of practical application of such solutions, in particular, the creation of individual learning trajectories that take into account the abilities, interests, and progress of each student, and automated assessment systems that provide prompt and objective feedback.The author pays special attention to the numerous advantages of integrating AI into the educational process. Among such advantages are the personalization of educational content, thanks to which students can receive knowledge at the optimal pace and format for them; increasing the accessibility of education, which helps overcome barriers for people with disabilities; as well as reducing the routine burden on teachers, who can devote more time to the creative and pedagogical aspects of their work.The article also examines in detail the challenges associated with the implementation of AI technologies in education. In particular, the emphasis is on the issues of ethical use of student data, the need to ensure the confidentiality of information and new roles of teachers in a technologically advanced learning environment. The author emphasizes the importance of transparent and inclusive algorithms that take into account the interests of all participants in the educational process, and also emphasizes the need to ensure a balance between the use of innovations and the preservation of traditional pedagogical values.A feature of this study is an interdisciplinary approach that allows combining technological, pedagogical and social aspects in studying the impact of AI on education. The article offers recommendations for a balanced implementation of AI in the educational process. Among them: the introduction of ethical control mechanisms, the active involvement of teachers and students in the development and testing of new systems, as well as ensuring access to educational technologies for all social groups.The author emphasizes the need for further research aimed at integrating AI into pedagogical practice without losing the human aspect. Such an approach will allow to fully reveal the potential of technologies, while preserving the uniqueness and importance of live interaction between teacher and student.This study is useful for a wide audience, in particular for scientists who analyze the impact of technologies on society; educators who seek to use AI more effectively in the educational process; and technology developers who create innovative solutions for education. The article demonstrates the current state of implementation of innovative technologies, identifies their advantages and disadvantages and outlines the prospects for further development in response to the dynamic needs of society in the field of education.
Keywords: Artificial intelligence; education; adaptive learning; technologies; privacy; innovation